Insurance and ESG: trends, challenges and future strategies - Edward, Oswald Timothy; Omar, Masitah (Universiti Teknologi MARA, Johor, 2025)
This article reviews recent academic research on the integration of Environmental, Social, and Governance (ESG) criteria within the insurance sector. Drawing upon systematic literature reviews and empirical studies, we examine how ESG is being incorporated into risk management, underwriting, asset management, governance, and product development. We identify key findings about the positive effects of ESG on firm performance and default risk, gaps in existing research, particularly in governance and social dimensions and challenges including data quality, regulatory alignment, and methodological inconsistency. Finally, we propose directions for future research and practical implications for insurers, regulators, and stakeholders. This review contributes to the broader conversation on sustainable finance, highlighting the insurance sector as both a risk absorber and an enabler of sustainability transitions. It further emphasizes the importance of integrating ESG not as a compliance obligation but as a transformative strategy capable of redefining risk management.